Privacy in medical emergency system: cryptographic and security aspects - Hameed, Shihab A.; Yuchoch, Habib; Al-Khateeb, Wajdi Fawzi Mohammed (2010)
Multilevel security is very important in Medical Emergency System MES since a database contained information with a variety of secret data. Information security was traditionally achieved by the use of encryption of data, but several stored and transmitted data in existing MES are not encrypted. This paper provides a classification of data sensitivity and suggests areas in cryptography to protect each data at different levels of sensitivity. There are two components in our work. The symmetric encryption AES with encryption key of an asymmetric algorithm (RSA). The symmetric key will be generated by application tier and be encrypted by RSA algorithm. The second component is asymmetric encryption (RSA) with client’s key pair generator. This paper shows the results of processing time of data encryption between asymmetric key algorithm (RSA) and symmetric key algorithm (AES) which includes its key-distribution processing time with client’s public key (RSA) from small to large amount of data. We measured the performance of four encryption algorithms (DES, 3DES, AES, and RSA) of our prototype distributed MES system. 256-bit symmetric keys are equivalent in strength to 15380-bit RSA keys. This discovery suggests that selecting appropriated algorithms for data encryption in different ranges of data size affects processing time supporting Medical Emergency System.